A Case of True Brachial Artery Aneurysm with Severe Left Upper Limb Ischemia - Nishimura, Kengo; Hamasaki, Takafumi; Fukino, Syunsuke (International Journal of Angiology, 2016)
Brachial artery (BA) aneurysms are rare, and most are false aneurysms. Although true BA aneurysms have been reported, most have been reported without symptoms. A 65-year-old man was referred due to a left upper limb mass with rest pain and slight ulceration of the left second and third fingers. As enhanced computed tomography revealed the patency of only the left proximal and distal BA as well as the thrombosed mass, excision of the aneurysm and BA replacement were performed with a great saphenous vein graft. The postoperative course was uneventful, and the rest pain and ulceration were resolved.
Keywords: upper limb ischemia; true brachial artery aneurysm; arteriovenous fistula